2007
DOI: 10.1007/s10840-006-9047-z
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous dual site left ventricular pacing plus biventricular pacing for the management of refractory ventricular tachycardia

Abstract: This is a case report of a male patient with nonischemic cardiomyopathy who had severely depressed left ventricular systolic function and functional class III congestive heart failure (CHF). He also had left bundle branch block (LBBB) and recurrent ventricular tachycardia (VT). Though the patient's CFH functional class improved after implantation of a transvenous biventricular ICD system, recurrent VT episodes required the initiation of amiodarone. After an improved condition for 28 months, recurrent VT episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Pappone et al [11] found that this mode of stimulation was superior to singlesite left ventricular pacing in terms of acute hemodynamic performance of the ventricle and its electrical synchrony. Until very recently, the only data on triple-site biventricular pacing came from anecdotal case-reports, which suggested that this type of stimulation can improve clinical status and suppress ventricular arrhythmias in HF patients [12][13][14]. In our previous study we demonstrated that dual left-single right cardiac resynchronization is a safe method and can be performed successfully in the majority of CRT candidates [7].…”
Section: Discussionmentioning
confidence: 94%
“…Pappone et al [11] found that this mode of stimulation was superior to singlesite left ventricular pacing in terms of acute hemodynamic performance of the ventricle and its electrical synchrony. Until very recently, the only data on triple-site biventricular pacing came from anecdotal case-reports, which suggested that this type of stimulation can improve clinical status and suppress ventricular arrhythmias in HF patients [12][13][14]. In our previous study we demonstrated that dual left-single right cardiac resynchronization is a safe method and can be performed successfully in the majority of CRT candidates [7].…”
Section: Discussionmentioning
confidence: 94%
“…Patients with narrow-complex were not included in this study. Acosta et al [9] described a case in which a patient with non-ischemic cardiomyopathy and LBBB developed an electrical storm despite having a biventricular ICD implanted and being on antiarrhythmic therapy [9]. Adding a new LV lead to provide multi-site LV pacing on top of BVP resulted in suppression of the ventricular arrhythmia, narrowing of the QRS complex, and improvement of HF functional class.…”
Section: Discussionmentioning
confidence: 99%
“…Dual‐site LV pacing has been described in the past using both epicardial and endocardial leads. It has been associated with decreased inter‐ and intra‐ventricular delay, 1 greater increases in peak dP/dt and pulse pressure, 2 improvement in ventricular tachycardias, 3 and in the largest series, the Trip‐HF study, decreased LV end‐systolic volume and increased LV ejection fraction 4 . However, in that study, only patients with permanent atrial fibrillation were eligible as it required plugging the second LV lead in the atrial port and pacing in a DDD mode with a 25‐ms atrioventricular interval to effect dual site LV pacing.…”
Section: Discussionmentioning
confidence: 99%